PENGARUH CORPORATE SIZE, PROFITABILITY, TENURE AUDIT, AUDITOR SPESIALIZATION, OWNERSHIP DISPERSION TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2016). - Claudia Aprilla Pardede; Adri Satriawan Surya; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to prove the factors that affect the audit delay. Factors tested in this study are corporate size, profitability, audit tenure, auditor specialization and ownership dispersion. The population of this research is the Banking companies listed in Indonesia Stock Exchange in 2014-2016. Total sample of this research is 38 companies with three years observation period so 114 observation objects have been selected. Data analysis was performed with the classical assumption and hypothesis testing using multiple linear regression method by SPSS version 17.00. The results indicates that the corporate size (SIZE), profitability (PROFIT) and ownership dispersion (DISPR) influence the audit delay. Meanwhile audit tenure (TENURE) and auditor specialization (SPEC) has no significant effect on audit delay. The influence of the independent variables to describe the dependent variable is 29,3%, while the remaining 70,7% is influenced by other variables.Keywords : Audit Delay, Corporate Size, Profitability, Audit Tenure, Auditor Specialization, Ownership Dispersion.